2013
DOI: 10.1017/s175173111200119x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding finisher pigs with chicory or lupine feed for one week or two weeks before slaughter with respect to levels of Bifidobacteria and Campylobacter

Abstract: This study aimed to assess whether inclusion of chicory or lupine (prebiotics) in the diet of pre-slaughter pigs for just 1 or 2 weeks could change the composition of their intestinal microbiota, stimulate the growth of bifidobacteria and help to lower the amount of thermoplilicCampylobacterspp. (mainlyCampylobacter jejuniandCampylobacter coli), which are a major cause of food-borne infections in humans. A total of 48 pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Although microbiome diversity increased dramatically in the piglets during the first few weeks of life, as reflected in previous studies 47,[50][51][52][53] , this was not associated with changes in AMR gene prevalence. We expected, as others have proposed, that changes in the microbiota would influence AMR gene levels 20,44,54 , but in fact the high levels of studied AMR genes in the young pigs reflected that of the farm's sow population. The most obvious explanation for this is a combination of vertical and horizontal transmission of bacteria at or shortly after birth 55,56 .…”
Section: Amr Gene Abundances Are High In Nursing Piglets With Low Micsupporting
confidence: 52%
See 1 more Smart Citation
“…Although microbiome diversity increased dramatically in the piglets during the first few weeks of life, as reflected in previous studies 47,[50][51][52][53] , this was not associated with changes in AMR gene prevalence. We expected, as others have proposed, that changes in the microbiota would influence AMR gene levels 20,44,54 , but in fact the high levels of studied AMR genes in the young pigs reflected that of the farm's sow population. The most obvious explanation for this is a combination of vertical and horizontal transmission of bacteria at or shortly after birth 55,56 .…”
Section: Amr Gene Abundances Are High In Nursing Piglets With Low Micsupporting
confidence: 52%
“…A previous cross-sectional study highlighted that only 10-42% of the variation in AMR gene levels could be explained by factors included in statistical models (including lifetime antimicrobial exposure), suggesting that AMR gene levels are strongly influenced by a variety of other elements 43 . Whilst these could be related to feed changes, the fact that the dry sows and young pigs were housed differently and fed different diets 44 would suggest that this effect is due to some other factors affecting the entire farm, such as housing and management 35,45,46 , environmental conditions 46 or the introduction of an infectious agent.…”
Section: Changes In Amr Gene Abundances Were Not Associated With Antimentioning
confidence: 99%
“…Although microbiome diversity increased dramatically in the piglets during the first few weeks of life, as reflected in previous studies (69, 72–75), this was not associated with changes in AMR gene prevalence. We expected, as others have proposed, that changes in the microbiota would influence AMR gene levels (27, 66, 76), but in fact the high levels of studied AMR genes in the young piglets reflected that of the sows. The most obvious explanation for this is a combination of vertical and horizontal transmission of bacteria at or shortly after birth (31, 77).…”
Section: Discussionsupporting
confidence: 58%
“…A previous cross-sectional study highlighted that only 10-42% of the variation in AMR gene levels could be explained by factors included in statistical models (including lifetime antimicrobial exposure), suggesting that AMR gene levels are strongly influenced by a variety of other elements (16). Whilst these could be related to feed changes, the fact that the sows and piglets were housed differently and fed different diets (66) would suggest that this effect is due to some other factors affecting the entire farm, such as housing and management (62, 67, 68), ambient temperature (68) and/or humidity, changes in water supply or the introduction of an infectious agent.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of feeding finisher pigs with chicory or lupin feed for one week or two weeks before slaughter with respect to levels of Bifidobacteria and Campylobacter were studied by Jensen et al (2013). This study showed that even a short-term alternative feeding strategy with probiotics in the diet of pre-slaughter pigs elicited changes in the composition of the intestinal microbiota, where lupin increased the level of bifidobacteria in the caecum and reduced the Campylobacter spp.…”
Section: Production Efficiency Of Lupin In Pigsmentioning
confidence: 98%